Core-Envelope model of einstein-Maxwell field equations under the influence of f (R) gravity - Mardan, S. A.; Khalid, A.; Riaz, Muhammad Bilal; Manzoor, Rubab (Elsevier, 2026)
This paper examines realistic configurations of anisotropic matter for spherical symmetry in modified gravity. With the Starobinsky f (R) = R+ aR2 model, the behavior of compact stars SAX J1808.4-3658 and 4U1608-52 in the presence of an electromagnetic field. A core-envelope model is developed with polytropic and linear equation of state (EoS). The core, envelope, and Reissner Nordstrom regions of compact stars match smoothly at the boundary. The graphs are plotted to discuss the physical behavior of density, pressure, mass, redshift, energy conditions, and compactification. To test stability of our model Tolman-Volkoff-Oppenheimer (TOV) equation and adiabatic index are presented graphically.
Keywords: Compact stars; Anisotropy; Core-envelope; f(R); Charge; EoS